THE IMPORTANCE OF BLOG IN WRITING LEARNING - ., Masri (NUR EL-ISLAM : Jurnal Pendidikan dan Sosial Keagamaan, 2017)
At this time, the development of Information and Communication Technology (ICT) in various fields is very rapid and seen as a necessity as well as an opportunity. In the field of education, for example, the development of ICT can provide a new dimension of literacy skills for learners; ICT is able to provide creative opportunities for young writers. Good writing skills are important for future learners. To start writing, learners can start from something simple and informal, such as journal/ diaries of everyday activities. However, the current writing study is still felt conventionally where the teacher still often tells the learner to make a writing directly without writing process. Often the topics are limited so they are less interesting, not challenging exploration, loss of innovation and creativity. In fact, teachers who often, during this time, be the only examiner of the letters writing so that the lack of feedback and interaction in the process of writing it. One way that can be used to improve the quality of learning and writing skills of learners by utilizing ICT is by blog (online journal). Blogs are an online journal where learners can write anything they find interesting, edit it, publish it, and even make it a media sharing for all those involved. It is believed that writing by blogging can provide a real and potential audience for better learner editing, innovation, exploration and creation, providing more dynamic interaction, better literacy skills, and even teamwork. Keywords: Blog, Writing Learning